Threats to animal life and Indonesian search for social-economic causes of forest fires - Fauziah, Saidatul (BKM Public Health and Community Medicine, 2021)
[ACCIDENTS DUE TO SOCIAL CONDITIONS] Impact on sufferers of the acute respiratory tract (ARI). Not only that, the existence of orangutans and other wildlife is also a threat. Therened. This process occurs during an unpredictable dry season, increasing the risk of forest and peatland fires. The results show that exposure to smog reduces health and education in the long term for children. It was found that in a day, the health service served about 50 to 70 patients with complaints of cough and shortness of breath due to smog. [COMMUNITY OR ORGANIZATION WHERE THE DISEASE PRODUCTION PROCESSES] Communities that have developed illegal oil palm plantations, illegal burning, and communities have not been able to switch to alternative livelihoods that are environmentally friendly. [“INTELLIGENCE” THAT ALLOWS SUCH SOCIAL CONDITIONS TO HAPPEN] Deliberately this happens because of group interests in commercial production. For example, peatland areas are used for new plantations, especially oil palm. [POWERFULNESS OF THE VICTIMS OF THAT SOCIAL CONDITION] It was found that the administrators of the farmer groups benefited greatly. The powerlessness of farmer groups in refusing the offers of certain actors risks harming the local community. These actors influence the decision-making process through their network of partners for their benefit. These farmer group administrators are protected by a network that provides strength, support, protection, and access to various resources. This condition is exacerbated by hot weather, causing land conditions to become drier, worsening the thickness of the smog, and the level of air pollution has reached "dangerous" levels. [ACTION THAT CAN REDUCE OR AGAINST THAT SOCIAL CONDITIONS] Forest fires are a continuing phenomenon year after year, and little progress has been made in reducing their incidence. Currently, the government is trying to issue a series of policies related to forest protection and peat restoration. The government is also trying to stop the issuance of new plantation permits in forest areas, restore damaged forests and peatlands and tackle land fires. The Task Force Team monitors peatland areas that are prone to fires, and patrols monitor the location points of peatlands. [KORBAN AKIBAT DARI KONDISI SOSIAL] Berdampak pada penderita saluran pernapasan akut (ISPA). Tidak hanya itu, keberadaan orang utan dan satwa liar lainnya juga terancam. Proses ini terjadi saat musim kering yang tidak bisa diperkirakan sehingga meningkatkan resiko kebakaran hutan dan lahan gambut. Hasil penelitian menunjukkan paparan asap kabut menurunkan Kesehatan dan Pendidikan dalam jangka panjang bagi anak-anak. Ditemukan dalam sehari layanan Kesehatan melayani sekitar 50 hingga 70 pasien dengan keluhan batuk dan sesak nafas akibat kabut asap. [KOMUNITAS ATAU ORGANISASI TEMPAT PROSES PRODUKSI PENYAKIT ITU] Masyarakat yang telah melakukan pengembangan perkebunan kelapa sawit illegal, pembakaran liar serta masyarakat belum dapat beralih ke mata pencaharian alternatif yang ramah lingkungan. [“KESENGAJAAN” YANG MEMBIARKAN KONDISI SOSIAL SEPERTI ITU TERUS TERJADI] Kesengajaan terjadi karena kepentingan golongan untuk produksi komersial contohnya area lahan gambut difungsinkan untuk perkebuanan baru, terutama kelapa sawit. [KETIDAK-BERDAYAAN KORBAN DARI KONDISI SOSIAL ITU] Ditemukan bahwa pengurus kelompok tani memperoleh manfaat besar.ketidakberdayaan kelompok tani dalam menolak tawaran aktor tertentu beresiko merugikan masyarakat setempat. Aktor-aktor ini mempengaruhi proses pengambilan keputusan melalui jarigan partonase mereka untuk kepentingan mereka sendiri. Pengurus kelompok tani ini lindungi oleh jaringan yang memberikan kekuatan, dukungan, perlindungan dan akses ke berbagai sumber daya. Kondisi ini diperparah dengan cuaca panas menyebabkan kondisi lahan semakin kering, memperparah ketebalan kabut asap dan tingkat polusi udara sudah mencapai level “berbahaya”. [AKSI YANG BISA MEGURANGI ATAU MELAWAN KONDISI SOSIAL ITU] Kebakaran hutan merupakan fenomena yang berlanjut dari tahun ke tahun dan hanya sedikit kemajuan yang dicapai dalam mengurangi kejadian. Saat ini pemerintah berupaya mengeluarkan serangkaian kebijakan terkait perlindungan hutan dan restorasi gambut. Pemerintah juga berupaya menghentkan pemberian izin baru perkebunan dikawasan hutan, memulihkan hutan serta lahan gambut yang rusak dan menanggulangi kebakaran lahan. Adapun pengawasan itu nantinya di monitor oleh tim satgas pada Kawasan lahan gambut yang rentan terjadi kebakaran serta patrol memantau titik-titik lokasi lahan gambut.